CHARACTERIZATION OF CALCIUM (Ca) BY USING SPECTROFOTOMETER UV-Vis FROM SIRIHLIME WITH CALCINATION METHODS OF MANGROVE CLAMSHELL IN KETAPANG - Adimarta, Trian; Nopriyanti, M (Jurnal Pertanian, 2020)
Clamshell is a solid waste generated by shells that are not utilized and cannot be consumed because they have hard properties. The purpose of this study was to determine the process of making sirihlime from mangrove shells using calcination method, characterizing calcium (Ca) using spectrophotometer UV-Vis.Method of making sirihlime from clamshell with calcination process. The calcination used was 1000oC for 3 hours, 800oC for 5 hours and 600oC for 7 hours. The results of the process of calcination of raw shells in the form of lime (CaO) and then added hot water to the Ca(OH)2 sirihlime was then characterized by calcium (Ca) using spectrophotometer UV-Vis 1800.Spectrofotometer UV-Vis of sirih lime demonstrated that maximum wavelength obtained is 529. The linier regression of the standart curve y = 1,021x + 1,6846 with a value of r2 = 0,7344. The calcium mineral from sirih lime at temperature 1000 oC for 3 hours an average of 1,536 mg/L, temperature 800oC for 5 hours an average of 2,2765 mg/L and temperature 600oC for 7 hours an average of 1,1159 mg/L.